The Existence Of Adat Law In Settlement Of Criminal Cases (Study in Gili Trawangan Tourism Area) - H Fatahullah; Israfil israfil (Unram Law Review, 2019)
This research purpose to determine to analysys the existence of adat law in settlement of criminal cases(in gili trawangan tourism area). The type of research used is empirical, by using the method of statute approach, conceprual approach and sociological approach. The result arequalified and exist in traditional offense Gili Trawangan general public in the form of: a. theft, b. Decency, adultery/cohabiting and infidelity, c. Preservation of marine ecosystems. Forms of traditional institutions of society Gili Trawangan, law enforcement organ composed of judges/ elders, lang-lang (customs security), and front Gili youth. Settlement of criminal cases for customary offenses is based on the provisions of the customary law of the Gili Trawangan society.